Risk of being undernourished in a cohort of community‐dwelling 85‐year‐olds: The Octabaix study. Issue 3 (2nd September 2013) - Farre, Teresa Badia; Formiga, Francesc; Ferrer, Assumpta; Plana‐Ripoll, Oleguer; Almeda, Jesus; Pujol, Ramon
<x xml:space="preserve">Abstract</x> Objectives To describe the prevalence of the risk of being undernourished in a community‐dwelling population of 85‐year‐olds, and to study associated factors. Methods A cross‐sectional community‐based survey of 328 inhabitants assigned to seven primary healthcare teams was carried out. Geriatric assessment was based on sociodemographic variables, the Barthel Index (BI), the Lawton Index (LI), the Spanish version of the Mini‐Mental State Examination, the Charlson Comorbidity Index, chronic diseases, social risk measured by Gijon's Social‐Familial Evaluation Scale, prescriptions and blood tests. Nutritional status was assessed using the Mini Nutritional Assessment (MNA). Participants were defined as being at risk of undernourishment when they had a MNA score above or equal to 23.5. A comparative analysis was carried out between patients with and without risk of being undernourished, and a multiple logistic regression analysis was carried out. Results The prevalence risk of being undernourished was 34.5%. A statistically significant association was found with being female (OR 2.44, 95% CI 1.28–4.54), LI (OR 1.47, 95% CI 1.29–1.66), social risk (OR 1.15, 95% CI 1.02–1.29) and prescription drugs taken (OR 5.58, 95% CI 2.09–14.92). Cardiovascular prescription showed a protective association (OR 4.34, 95% CI 1.78–10.0). No statistical differences between the risks of being undernourished were found in the laboratory analysis. Conclusions There is a high risk of being undernourished in 85‐year‐old subjects. This nutritional status was positively associated with being female, disability, increased social risk and a high number of prescription drugs, whereas there was a protective relationship with cardiovascular prescription. In evaluations of nutritional status in the community, a multidisciplinary assessment is more valid than analytical findings. Geriatr Gerontol Int 2014; 14: 702–709.